2021
DOI: 10.1002/chem.202004208
|View full text |Cite
|
Sign up to set email alerts
|

Not‐So‐Innocent Anions Determine the Mechanism of Cationic Alkylators

Abstract: Alkylating reagents based on thioimidazolium ionic liquids were synthesized and the influence of the anion on the alkylation reaction mechanism explored in detail using both experimental and computational methods. Thioimidazolium cations transfer alkyl substituents to nucleophiles, however the reaction rate was highly dependent on anion identity, demonstrating that the anion is not innocent in the mechanism. Detailed analysis of the computationally‐derived potential energy surfaces associated with possible mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…We see similar deviations from the ideal for the electron-poor benzimidazole and even in the geometry of the nitro group with the benzimidazole. Surprisingly, we do not predict any dissociation of the counterions from bMeBAB in DMSO even for 7 , despite this generally arising in our studies of other ion-paired systems. ,, …”
Section: Results and Discussioncontrasting
confidence: 81%
“…We see similar deviations from the ideal for the electron-poor benzimidazole and even in the geometry of the nitro group with the benzimidazole. Surprisingly, we do not predict any dissociation of the counterions from bMeBAB in DMSO even for 7 , despite this generally arising in our studies of other ion-paired systems. ,, …”
Section: Results and Discussioncontrasting
confidence: 81%
“…Pyridine reacted far faster with CH 3 I at room temperature in comparison to IL‐2 a , but this stark different was not observed with thiophenol (Tables S2 and S3). These results suggest a different reaction mechanism for the alkylation of thiolates using thioimidazolium salts than for pyridine [8b] . A possible explanation for the high observed reactivity is the encapsulation of the two reacting species in a reaction pocket.…”
Section: Resultsmentioning
confidence: 85%
“…Such results are consistent with what we have previously shown in our study of the small molecule system. In that study, the role of ion‐pairing differences in a series complexes with various anions in changing the reaction mechanism were highlighted [8b] . Specifically, we showed that an iodide‐based alkylating ionic liquid reacts with nucleophiles via a 2‐step mechanism, which involves the in‐situ formation of CH 3 I.…”
Section: Resultsmentioning
confidence: 93%
“…Taking classical methylation as an example, methylation of thioureas has traditionally been carried out using unstable, volatile, or toxic methylating agents . Alternatively, sulfuric esters can be used as an alkylation source as well, but they are generally highly toxic and explosive . The use of phosphates and phosphorothioates as methylation reagents has also gained popularity in the last few decades .…”
Section: Introductionmentioning
confidence: 99%